2018
DOI: 10.1177/1945892418787116
|View full text |Cite
|
Sign up to set email alerts
|

The Dermatophagoides pteronyssinus Molecular Sensitization Profile of Allergic Rhinitis Patients in Central China

Abstract: Background House dust mites (HDMs) are the major aeroallergens in patients with rhinitis and/or asthma in China. However, the molecular sensitization of HDM is varied in different regions. Objective To investigate the Dermatophagoides pteronyssinus ( Der p) molecular sensitization profile of allergic rhinitis (AR) patients in Central China. Methods AR patients with positive skin prick tests to Der p were enrolled in our study. Specific immunoglobulin E (sIgE) for Der p, Dermatophagoides farinae ( Der f), Acaru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…6 Some studies have reported a moderate correlation between Der p and Blo t through analysis of the levels of specific IgE (sIgE). [6][7][8] However, partial IgE inhibition assays have shown that Blo t allergens have little cross-reactivity with Der p and Der f. [9][10][11] At present, studies about cross-reactivity between Blo t and Der p and Blo t and Der f are few and appear to be inconsistent. Whether patients co-sensitized to Blo t and the other two mites are due to true sensitization or cross-reaction is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…6 Some studies have reported a moderate correlation between Der p and Blo t through analysis of the levels of specific IgE (sIgE). [6][7][8] However, partial IgE inhibition assays have shown that Blo t allergens have little cross-reactivity with Der p and Der f. [9][10][11] At present, studies about cross-reactivity between Blo t and Der p and Blo t and Der f are few and appear to be inconsistent. Whether patients co-sensitized to Blo t and the other two mites are due to true sensitization or cross-reaction is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact of great homology between DPT and the rest of the mites belonging to the family Pyroglyphidae, (15,16,23) allergy clinicians commonly prescribe mixed vaccines to treat patients polysensitized to mites. As it was mentioned, the most common mites with positive results in diagnostic prick tests performed in patients with respiratory allergy in Spain, were DPT, DF and Lepidoglyphus destructor (6), excluding the islands.…”
Section: Discussionmentioning
confidence: 99%
“…According to EMA guidelines, mixture of different allergenic sources is only recommended when they are taxonomically related (14). In the case of DPT and DF mixture, the similarity and cross-reactivity is so high, between 80 -90 % (15,16) that it could be enough to receive unique vaccine with one of these two allergen extracts. As a consequence of the enormous homology, any of the two allergenic sources could be proposed as the representative homologous specie (17).…”
Section: A N U S C P R I T a C C E P T E D F O R P U B B L I C A T mentioning
confidence: 99%
“…6 In another example of how molecular markers differ in subsets of patients with the same disease process, Yang et al showed differences in molecular sensitization profiles to Dermatophagoides pteronyssinus in allergic rhinitis (AR) patient with and without concomitant asthma. 7 AR patients with asthma were also shown to have a significantly higher concentration of serum immunoglobulin E to D. pteronyssinus compared to nonasthmatics. 7 Studies like those by Guo et al 6 and Yang et al 7 highlight the importance of finding molecular markers that repeatedly and reliably identify specific subsets of patients who may stand to gain the most clinically from use of a particular biologic and also guide treatment choice.…”
mentioning
confidence: 94%
“…7 AR patients with asthma were also shown to have a significantly higher concentration of serum immunoglobulin E to D. pteronyssinus compared to nonasthmatics. 7 Studies like those by Guo et al 6 and Yang et al 7 highlight the importance of finding molecular markers that repeatedly and reliably identify specific subsets of patients who may stand to gain the most clinically from use of a particular biologic and also guide treatment choice.…”
mentioning
confidence: 94%